Pea and Barley Forage as Fallow Replacement for Dryland Wheat Production. (1st May 2018) - Miller, Perry; Glunk, Emily; Holmes, Jeff; Engel, Richard
Abstract : Core Ideas: Forage yields from pea, especially winter pea, were competitive with hay barley yields. Crude protein yield from pea forage was 40 to 110% greater than barley. Crop harvest at the bloom stage used the least soil water and nitrogen. Wheat yield following pea averaged 82 to 88% of that on chemical fallow. There is a growing interest in the use of annual forages in rotation with wheat ( Triticum aestivum L.). The objectives of this study were to: (i) compare forage yield and quality of spring and winter pea ( Pisum sativum L.), barley ( Hordeum vulgare L.), and a pea–barley mixture harvested at flowering (early), pod (late), or grown to maturity; and (ii) compare the cropping‐sequence effects of these cropping treatments for three N fertilizer rates, subsequent wheat yield, and grain quality relative to chemical fallow. This study was conducted at Amsterdam, MT, from 2003 to 2006. Pea forage yield at the pod stage was 1.2 Mg ha −1 (30%) and 3.7 Mg ha −1 (60%) greater than at the flower stage for spring and winter pea, respectively. At the same harvest times, spring barley forage averaged 1.8 Mg ha −1 (32%) greater either as a sole species or when mixed with spring pea. Forage quality of pea forage was high regardless of harvest timing. Protein yield for spring and winter pea forage averaged 0.28 (60%) and 0.38 Mg ha −1 (81%) greater than the barley forage treatments across harvest times and years. Significant differences in stored soil water (19 mm) and soil nitrate N (10 kg N ha −1 ) were found between flowering and pod forage harvest timing in pea, but these differences only nominally affected subsequent wheat yield or quality. Wheat following pea averaged approximately 85% of the yield on chemical fallow. Among the cropping treatments, the greatest wheat yield and protein occurred following winter pea harvested at the flower stage.